Causes, Consequences and Policy implications of Squatter Settlement in Gondar Town in the Case of Kebele 18 - Gebeyehu, Kelemu Fenta (Innovare Journal of Social Sciences, 2016)
AbstractÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Objective: the principal objective of the study is to assess the causes and consequences of squatter settlements in the light of unplanned expansion of the built-up area and policy responses to it. Methods: in order to achieve the study objective, in-depth interview with 20 household heads and municipal administrators' documentary analysis and observational techniques were used.Â Results: major findings of the study indicate that emergence of squatter settlements in the study area is a recent phenomenon that has occurred since 2005. High building standards of the legal houses, delayed responses, and procedural problems of the legal land provision, and high housing rents in the city centre were identified by respondents as the causes of squatting in the study area. In addition, less government control of open spaces, the limited capacity of the code enforcement service to control illegal house construction, lack of a comprehensive legal response towards the problem of squatting, and the practice of land sale by land speculators as a means of making profit are other factors that have contributed to the emergence and proliferation of squatter settlements. Compared to the plot sizes of the legal land provision, the plot sizes of the squatter settlements in the study area are large and there are undeveloped vacant fenced plots between squatter housing units. Thus, land in the area is inefficiently exploited and the situation has greatly contributed to the unplanned and rapid horizontal expansion of the built-up area of the town. Â Keywords: Squatter settlement, policy implications and illegal house